The Influence of Cash Conversion Cycle, Company Size, and Leverage on Company Profitability : Study on Automotive Distributor Company PT. New Ratna Motor Semarang (Nasmoco Group) 2021-2024 - Afif Raihan Andika Putra; Harjum Muharam (PT. Maju Malaqbi Makkarana, 2026)
This study discusses the optimization of a company's financial performance through working capital management and capital structure policies. To increase profitability (ROA), companies require efficient cash conversion cycle management and optimal funding supported by internal company characteristics. The research problem proposed is to determine how to achieve increased profitability in an automotive distributor company through the efficiency factors of Cash Conversion Cycle (CCC), Firm Size (Firm Size), Leverage (DER), and historical profitability factors (ROA_Lag). The sample of this study is the financial statements of PT New Ratna Motor (Nasmoco Group) in Semarang City for the 2021-2024 period, which were transformed into quarterly data (N=16). The results of data analysis indicate that this research model has a good level of feasibility (goodness of fit) with the ability to explain variations in profitability (Adjusted R Square) of 78.1% and successfully overcome autocorrelation interference. Simultaneously, there is a strong relationship between the independent variables and the company's profit movements. Partially, the Cash Conversion Cycle (CCC) variable is proven to have a negative and significant effect on profitability, while the Firm Size and Leverage variables have not shown a significant effect at the 95% confidence level.